Population-Based Assessment of the Incidence of Aortic Dissection, Intramural Hematoma, and Penetrating Ulcer, and Its Associated Mortality From 1995 to 2015. Issue 8 (August 2018) - DeMartino, Randall R.; Sen, Indrani; Huang, Ying; Bower, Thomas C.; Oderich, Gustavo S.; Pochettino, Alberto; Greason, Kevin; Kalra, Manju; Johnstone, Jill; Shuja, Fahad; Harmsen, W. Scott; Macedo, Thanila; et al.
Abstract : Background: Aortic syndromes (ASs), including aortic dissection, intramural hematoma, and penetrating aortic ulcer, carry significant acute and long-term morbidity and mortality. However, the contemporary incidence and outcomes of AS are unknown. Methods and Results: We used the Rochester Epidemiology Project record linkage system to identify all Olmsted County, MN, residents with AS (1995–2015). Diagnostic imaging, medical records, and death certificates were reviewed to confirm the diagnosis and AS subtype. Age- and sex-adjusted incidence rates were estimated using annual county-level census data. Survival for patients with AS was compared with age- and sex-matched controls using Cox regression to adjust for comorbid conditions. We identified 133 patients with AS (77, aortic dissection; 21, intramural hematoma; and 35, penetrating aortic ulcer). Average age was 71.8 years (SD=14.1), and 57% were men. The age- and sex-adjusted incidence was 7.7 per 100 000 person-years, was higher for men than women (10.2 versus 5.7 per 100 000 person-years), and increased with age. Among subtypes, the incidence of aortic dissection was highest (4.4 per 100 000 person-years), whereas the incidence of penetrating aortic ulcer and intramural hematoma was lower (2.1 and 1.2 per 100 000 person-years). Overall, the incidence of AS was stable over time ( P trend=0.33), although the incidence of penetrating aortic ulcer seemed to increase from 0.6 to 2.6 per 100 000 person-years ( P =0.008) with variability over the study interval. Patients with AS had more than twice the mortality rate at 5, 10, and 20 years when compared with population-based controls (5-, 10-, and 20-year mortality 39%, 57%, and 91% versus 18%, 41%, and 66%; overall adjusted mortality hazards ratio=2.1; P <0.001). Survival was lower than expected up to 90 days after AS diagnosis and did not differ significantly by subtype or by 5-year strata of diagnosis. Conclusions: Overall, the incidence of aortic dissection and intramural hematoma has remained stable since 1995, despite the decline noted for other cardiovascular disease. AS confers increased early and long-term mortality that has not changed. These data highlight the need to improve long-term care to impact the prognosis of this patient group. Abstract : Supplemental Digital Content is available in the text.